µ-BENZENE-1,2,4,5-TETRACARBOXYLATO-κ2O1:O4)BIS[ AQUABIS- 2-(AMINOMETHYL) PYRIDINE-κ2N,N’) NICKEL (II)] DECAHYDRATE: STRUCTURE AND MAGNETIC PROPERTIES - Atria, Ana María; Parada, José; Baggio, Ricardo; Peña, Octavio; Moreno, Yanko (Journal of the Chilean Chemical Society, 2019)
µ-Benzene-1,2,4,5-tetracarboxylato-κ2O1:O4)bis[aquabis-2-(aminomethyl) pyridine-κ2N,N’) nickel (II)] decahydrate, [Ni2(amp)4(btc)(H2O)2].10H2O has been synthesized and its crystal structure determined by X-ray diffraction. The complex crystallizes in the Monoclinic space group P21/n with cell dimensions a= 11.0102 (10) Å, b= 21.5416 (19) Å, c= 11.0445 (10) Å and ß= 118.753 (1)°, and two formula units per cell (Z= 2, Z’= 0.5). The structure consists of centrosymmetric dimeric units in which the benzene tetracarboxylate anions (btc) bridge the symmetry–related nickel (II) cations, two bidentate chelating molecules of 2-(aminomethyl) pyridine and a terminal aqua ligand completing the six-fold coordination at each metal. These dimers link to each other via H-bonding to form chains parallel to [100], while the water solvates form a strongly bound 2D network parallel to (100), made up by small (R44(8) ) and large (R20 20(40)) rings, the latter ones “pierced” by the chains of dimmers, with a profuse H-bonding interconnection between both substructures. Magnetic susceptibility measurements as a function of temperature disclose weak interdimeric exchange interactions. Fitting of these data to a dimeric model yields J= -3.5 cm-1 and g= 2.13.